Challenges in the diagnosis of gastroesophageal reflux disease in infants and children. (May 2013) - Vandenplas, Yvan
<x xml:space="preserve">Abstract</x> Introduction: The diagnosis of gastroesophageal reflux disease (GERD) is challenging. The wide variation in symptoms is a major reason for the controversies. Since the expression of GERD varies from nonerosive reflux disease over Barrett's esophagus to chronic respiratory disease, it is clear that not one investigation technique will provide an answer in all situations. Areas covered: Relevant literature published in PubMed and CINAHL and recent guidelines were collected and reviewed. Diagnostic tests were evaluated by the following criteria: ability to confirm a diagnosis, to exclude other diagnoses with similar presentation, to detect complications, to predict disease severity. Expert opinion: Multiple intraluminal impedance (MII) is extensively evaluated in recent years, but other new techniques and measurements were also developed, mainly to diagnose extra-esophageal symptoms. Although evidence for a "relation" between GER and extra-esophageal symptoms is demonstrated, the "causality" between both is not proven. MII measures in a reliable reproducible way non-acid or weakly acid reflux. However, as long as medical therapeutic options are limited to anti-acid medications, MII lacks therapeutic implications, and therefore clinical impact. Since investigations for GER are invasive or cause irradiation, normal ranges cannot be established. As a consequence, the "old" techniques remain the standard diagnostic tools: barium meal for anatomy, endoscopy for esophagitis, and pH monitoring to demonstrate a time relation between (acid) GER and symptoms. MII provides more information than pH monitoring, but is more expensive and has limited therapeutic impact as long as drugs are mainly "anti-acid."